The Effect of Extensive Feeding Systems on Growth Rate, Carcass Traits, and Meat Quality of Finishing Lambs - De Brito, Gerlane F.; Ponnampalam, Eric N.; Hopkins, David L. (Wiley, 2017)
This review aims to summarize the relevant published information about the effects of extensive feeding systems on the carcass and meat quality characteristics of lambs. Lambs finished in a feedlot or with supplementation under extensive systems exhibit faster growth rates, achieve target weights quicker, and produce heavier carcass weights when compared to grazing lambs. However, the literature also shows that finishing lambs on high-quality pasture can produce satisfactory growth rates without compromising carcass and meat quality traits. Lately, the consumer demand for products perceived as “healthy” and that are produced where animal welfare is optimal under systems which do not impact negatively on the environment, has heightened the interest in lamb production under extensive systems. Lambs raised on pasture can meet many of these specifications. Also, lambs fed higher quality green pasture can produce meat with greater amounts of health-claimable omega-3 fatty acids such as eicosapentaenoic acid plus docosahexaenoic acid than feeding systems based on feedlot pellets, grain, or dry pasture/straw. It is apparent that in some previous published research, the number of animals allocated for each treatment, and the lack of replicates, makes it difficult to formulate a correct understanding of the effect of forages on lamb carcass and meat quality. Future research should concentrate on the effect of legume, improved pasture, and specialized forage finishing systems on growth rate, carcass traits, and nutritional value of meat using well-designed experiments with an adequate number of lambs and appropriate paddock replicates per treatment.
Keywords: forage; meat quality; production system; sheep; supplementation